2013
DOI: 10.3899/jrheum.120941
|View full text |Cite
|
Sign up to set email alerts
|

Longterm Outcomes and Treatment After Myocardial Infarction in Patients with Rheumatoid Arthritis

Abstract: Objective To investigate the risk profiles, treatment utilization, and outcomes of myocardial infarction (MI) patients with rheumatoid arthritis (RA) and matched MI patients without RA. Methods We utilized a population-based cohort of Olmsted County, Minnesota, residents with MI from 1979–2009. Among these, we identified 77 patients who fulfilled the American College of Rheumatology (ACR) 1987 criteria for RA and 154 age, sex, and calendar year matched MI patients without RA. Data collection from medical rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 32 publications
2
39
0
1
Order By: Relevance
“…Further, despite similar treatment, patients with RA who had a myocardial infarction had worse long-term outcomes than those without RA 31. This deficiency in CVD risk management is amply confirmed in an investigation of CVD risk factor control in 836 patients with RA by Primdahl and colleagues 32.…”
Section: Cvd Preventionmentioning
confidence: 90%
“…Further, despite similar treatment, patients with RA who had a myocardial infarction had worse long-term outcomes than those without RA 31. This deficiency in CVD risk management is amply confirmed in an investigation of CVD risk factor control in 836 patients with RA by Primdahl and colleagues 32.…”
Section: Cvd Preventionmentioning
confidence: 90%
“…No previous studies of post-MI prognosis in patients with IBD have been reported, but the association between IBD and worsened prognosis after MI is in line with findings in other chronic inflammatory diseases, including rheumatoid arthritis and psoriasis. 25,26 The observation of a relationship between adverse cardiovascular events and active stages of IBD further suggests that inflammation plays a central role in the association between IBD and atherothrombotic events. Indeed, the arterial and systemic immune-inflammatory processes implicated in atherosclerosis and atherothrombotic events bear many resemblances to the intestinal and systemic inflammation seen in active IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies over last 20 years showed that patients with RA have significantly higher risk of coronary heart disease (CHD) when compared with non-RA subjects. Patients with RA are more likely to experience unrecognized myocardial infarction and sudden death and, they also have poorer long-term outcomes than those with myocardial infarction without RA [10,17]. The influence of traditional risk factors and chronic systemic inflammation is described in this article.…”
Section: Introductionmentioning
confidence: 97%